A method for preparing fire-resistant and stain-resistant SPC floor
Through the glue bonding and cold pressing of the modified EVA sheet and the SPC substrate, combined with sheet magnesium hydroxide and modified nano-silica, the problem of insufficient fire resistance and stain resistance of SPC floors is solved, and the further development is achieved. High fire resistance and stain resistance.
Patent Information
- Application Number
- CN202410866906.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-01
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-07-01
AI Technical Summary
The existing SPC floors have poor fire resistance and stain resistance, which leads to difficulty in cleaning.
The modified EVA sheet is bonded with the SPC substrate by glue and cold pressing, and sheet-like magnesium hydroxide and modified nanosilicon dioxide are introduced into the modified EVA sheet.
The fire resistance, mechanical properties and stain resistance of SPC floors are significantly improved, and the combination of modified EVA sheets and SPC substrates enhances the overall performance of the floor.
Smart Images

Figure CN118832889B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fire-resistant floors, and in particular to a method for preparing a fire-resistant and stain-resistant SPC floor. Background Art
[0002] Flooring is the surface layer of the ground or floor of a house. It is made of wood or other materials. There are many types of flooring. According to the structure, there are: solid wood flooring, laminate flooring, three-layer solid wood composite flooring, bamboo flooring, anti-corrosion flooring, cork flooring and the most popular multi-layer solid wood composite flooring; according to the use, there are: home use, commercial use, anti-static flooring, outdoor flooring, stage dance flooring, sports hall flooring, track and field flooring, etc.; according to the environmental protection level, there are: E0 flooring, E1 flooring, F4 flooring, JAS star standard F4 star flooring, etc.
[0003] SPC floor (Stoneplast iccomposite) is a type of floor, that is, stone plastic floor, which is a new type of decorative floor material.
[0004] The base material of SPC floor is a composite board made of stone powder and thermoplastic polymer material which is evenly mixed and then extruded at high temperature. It has high strength and toughness.
[0005] However, most SPC floors on the market currently have relatively poor stain resistance and fire resistance, which makes SPC floors difficult to clean.
[0006] Based on this, we proposed a method for preparing fire-resistant and stain-resistant SPC flooring, hoping to solve the shortcomings of the existing technology. Summary of the invention
[0007] 1. Technical issues to be solved
[0008] In view of the deficiencies in the prior art, the present invention provides a method for preparing a fire-resistant and stain-resistant SPC floor.
[0009] (II) Technical solution
[0010] To achieve the above-mentioned purpose, the present invention provides the following technical solutions:
[0011] A method for preparing a fire-resistant and stain-resistant SPC floor, which is made by laminating a modified EVA sheet with an SPC substrate;
[0012] Wherein, the modified EVA sheet and the SPC substrate are bonded by gluing;
[0013] The gluing is performed by using an adhesive;
[0014] The modified EVA sheet and the SPC substrate are bonded and then cold pressed.
[0015] As a further technical solution, the modified EVA sheet preparation method comprises the following steps:
[0016] (1) adding ethylene-vinyl acetate copolymer, modified nano titanium dioxide, flaky magnesium hydroxide, and an organic silane coupling agent to a mixer in sequence, stirring and mixing, and obtaining a mixed material;
[0017] (2) placing the mixed material obtained in step (1) in a drying oven for drying to obtain a dry material;
[0018] Among them, the drying temperature is 80°C and the time is 2 hours;
[0019] (3) adding the dried material obtained in step (2) to a double-roll mill for refining to obtain a refining material;
[0020] (4) adding the raw material obtained in step (3) to a flat vulcanizing machine for tableting to obtain an EVA sheet;
[0021] (5) The EVA sheet obtained in step (4) is subjected to electron beam irradiation treatment under vacuum, and then discharged to obtain a modified EVA sheet.
[0022] As a further technical solution, the mass ratio of the ethylene-vinyl acetate copolymer, modified nano titanium dioxide, flaky magnesium hydroxide and organic silane coupling agent in step (1) is 70-78:10-14:4-6:1-1.2.
[0023] As a further technical solution: the preparation method of the modified nano titanium dioxide is:
[0024] Add palmitic acid and maleic acid to the ethanol solution in sequence, and stir and mix at a speed of 120 r / min for 30 min to obtain a treated solution;
[0025] Add nano-titanium dioxide and nano-silicon dioxide to the treatment solution in sequence, stir at 550 r / min for 2 hours, and let stand for 20 minutes;
[0026] The mixture was then ultrasonically treated for 10 minutes, filtered and dried to obtain modified nano titanium dioxide.
[0027] As a further technical solution, the mass ratio of the palmitic acid, maleic acid and ethanol solution is 3-4:1-1.5:12;
[0028] The mass fraction of the ethanol solution is 90%;
[0029] The mixing ratio of the treatment liquid, nano titanium dioxide and nano silicon dioxide is 200 mL: 20-30 g: 2-3 g.
[0030] As a further technical solution, the ultrasonic frequency is 40kHz and the power is 500W.
[0031] As a further technical solution: in step (3), the refining treatment time is 15-16 minutes and the temperature is 104-106°C.
[0032] As a further technical solution: in step (4), the temperature of the sheeting on the flat vulcanizing machine is 116-118° C. and the time is 12-15 minutes.
[0033] As a further technical solution: in step (5), the vacuum condition is 0.1-0.2 Pa;
[0034] The dose of electron beam irradiation treatment is 100-120 kGy, and the dose rate is 180 kGy / min.
[0035] As a further technical solution: the adhesive is a two-component polyurethane glue, and the glue amount is 80-100g / ㎡;
[0036] The cold pressing pressure is 1-2MP and the time is 2.5 hours.
[0037] (III) Beneficial effects
[0038] Compared with the prior art, the present invention provides a method for preparing a fire-resistant and stain-resistant SPC floor, which has the following beneficial effects:
[0039] The SPC floor prepared based on the SPC substrate of the present invention not only has excellent fire resistance, but also has excellent stain resistance.
[0040] The surface of the SPC floor prepared by the present invention is protected by a modified EVA sheet. Compared with conventional EVA sheets, the modified EVA sheet prepared by the present invention improves the fire resistance, mechanical properties and stain resistance of the floor to varying degrees.
[0041] The present invention introduces flaky magnesium hydroxide into the modified EVA sheet material, which can be closely combined with EVA in the EVA system, thereby greatly improving the flame retardant effect of the floor. When the floor burns, a dense carbon layer can be quickly generated. The formed carbon layers can not only effectively suppress the release of smoke, toxic gas and heat, thereby achieving a good smoke suppression effect, but also can block oxygen, hinder the transmission of heat and combustible gas, thereby achieving a good flame retardant effect.
[0042] The present invention introduces modified nano silicon dioxide into the EVA sheet material, and the surface water contact angle of the modified EVA sheet material can be significantly improved by the introduction of the modified nano silicon dioxide. This is mainly because the nano silicon dioxide is modified so that the modified nano silicon dioxide obtained after the modification can not only significantly improve the compatibility in the EVA sheet material system, but also form hydrogen bonds with the EVA sheet material system and form hydrophobic groups on the surface of the modified EVA sheet material, thereby significantly improving the surface water contact angle of the modified EVA sheet material, and significantly improving the surface stain resistance of the modified EVA sheet material, thereby significantly improving the stain resistance of the manufactured SPC floor material.
[0043] The introduction of flaky magnesium hydroxide and modified nano-silicon dioxide also improves other functions of modified EVA sheets, including:
[0044] Improved mechanical properties:
[0045] Flaky magnesium hydroxide and modified nano-silicon dioxide help to improve the strength, hardness and tensile properties of the modified EVA sheet, and mainly play the role of enhancing the strength of the modified EVA sheet.
[0046] Improve thermal stability:
[0047] Flaky magnesium hydroxide and modified nano-silicon dioxide exhibit good thermal stability at high temperatures and can improve the fire resistance of modified EVA sheets.
[0048] Increase wear resistance:
[0049] Adding flaky magnesium hydroxide and modified nano-silicon dioxide can improve the wear resistance of the modified EVA sheet and increase the service life of the manufactured floor. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 A flow chart of a method for preparing a fire-resistant and stain-resistant SPC floor;
[0051] Figure 2 It is a bar chart of fire resistance performance of the samples in the examples. DETAILED DESCRIPTION
[0052] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0053] A method for preparing a fire-resistant and stain-resistant SPC floor, which is made by laminating a modified EVA sheet with an SPC substrate;
[0054] Wherein, the modified EVA sheet and the SPC substrate are bonded by gluing;
[0055] The gluing is performed by using an adhesive;
[0056] The modified EVA sheet and the SPC substrate are bonded and then cold pressed.
[0057] The adhesive is a two-component polyurethane glue with a glue amount of 80-100g / ㎡;
[0058] The cold pressing pressure is 1-2MP and the time is 2.5 hours. During the cold pressing, be sure to remove the air and avoid any defects such as bulging, loose edges and delamination.
[0059] Before lamination, the surface of the SPC substrate is sanded and the thickness is adjusted to 4.5±0.05mm;
[0060] After cold pressing, let it stand for more than 8 hours to cure until the glue is completely cured. The curing temperature can be selected at 30℃.
[0061] The modified EVA sheet preparation method comprises the following steps:
[0062] (1) Adding ethylene-vinyl acetate copolymer, modified nano titanium dioxide, flaky magnesium hydroxide, and an organic silane coupling agent to a mixer in sequence, stirring and mixing, and obtaining a mixed material; the mixing mass ratio of the ethylene-vinyl acetate copolymer, modified nano titanium dioxide, flaky magnesium hydroxide, and organic silane coupling agent is: 70-78:10-14:4-6:1-1.2; the preparation method of modified nano titanium dioxide is:
[0063] Add palmitic acid and maleic acid to the ethanol solution in sequence, and stir and mix at a speed of 120 r / min for 30 min to obtain a treated solution;
[0064] Add nano-titanium dioxide and nano-silicon dioxide to the treatment solution in sequence, stir at 550 r / min for 2 hours, and let stand for 20 minutes;
[0065] The mixture was then ultrasonically treated for 10 minutes, filtered and dried to obtain modified nano titanium dioxide.
[0066] The mass ratio of palmitic acid, maleic acid and ethanol solution is 3-4:1-1.5:12;
[0067] The mass fraction of the ethanol solution is 90%;
[0068] The mixing ratio of the treatment liquid, nano titanium dioxide and nano silicon dioxide is 200 mL: 20-30 g: 2-3 g; the ultrasonic frequency is 40 kHz and the power is 500 W.
[0069] The molecular formula of ethylene-vinyl acetate copolymer in the embodiment is (C2H4)2.(C4H6O2)4;
[0070] In the embodiment, the organic silane coupling agent used is vinyltrimethoxysilane.
[0071] (2) placing the mixed material obtained in step (1) in a drying oven for drying to obtain a dry material;
[0072] Among them, the drying temperature is 80°C and the time is 2 hours;
[0073] (3) adding the dried material obtained in step (2) to a double-roll mill for refining to obtain a refining material; the refining time is 15-16 minutes, and the temperature is 104-106°C.
[0074] (4) adding the raw material obtained in step (3) to a flat vulcanizer for tableting to obtain an EVA sheet; the tableting temperature on the flat vulcanizer is 116-118° C. and the time is 12-15 min.
[0075] (5) subjecting the EVA sheet obtained in step (4) to electron beam irradiation treatment under vacuum, and then discharging the sheet to obtain a modified EVA sheet; the vacuum condition is 0.1-0.2 Pa;
[0076] The dose of electron beam irradiation treatment is 100-120 kGy, and the dose rate is 180 kGy / min.
[0077] The following are specific embodiments:
[0078] Example 1
[0079] A method for preparing a fire-resistant and stain-resistant SPC floor, which is made by laminating a modified EVA sheet with an SPC substrate;
[0080] Wherein, the modified EVA sheet and the SPC substrate are bonded by gluing;
[0081] The gluing is performed by using an adhesive;
[0082] The modified EVA sheet and the SPC substrate are bonded and then cold pressed.
[0083] The adhesive is a two-component polyurethane glue with a glue amount of 80g / ㎡;
[0084] The cold pressing pressure is 1 MP and the time is 2.5 hours.
[0085] Before lamination, the surface of the SPC substrate is sanded and the thickness is adjusted to 4.5±0.05mm;
[0086] The modified EVA sheet preparation method comprises the following steps:
[0087] (1) Adding ethylene-vinyl acetate copolymer, modified nano titanium dioxide, flaky magnesium hydroxide, and an organic silane coupling agent to a mixer in sequence, stirring and mixing, and obtaining a mixed material; the mixing mass ratio of the ethylene-vinyl acetate copolymer, modified nano titanium dioxide, flaky magnesium hydroxide, and organic silane coupling agent is 70:10:4:1; the preparation method of modified nano titanium dioxide is:
[0088] Add palmitic acid and maleic acid to the ethanol solution in sequence, and stir and mix at a speed of 120 r / min for 30 min to obtain a treated solution;
[0089] Add nano-titanium dioxide and nano-silicon dioxide to the treatment solution in sequence, stir at 550 r / min for 2 hours, and let stand for 20 minutes;
[0090] The mixture was then ultrasonically treated for 10 minutes, filtered and dried to obtain modified nano titanium dioxide.
[0091] The mass ratio of palmitic acid, maleic acid and ethanol solution is 3:1:12;
[0092] The mass fraction of the ethanol solution is 90%;
[0093] The mixing ratio of the treatment liquid, nano titanium dioxide and nano silicon dioxide is 200 mL: 20 g: 2 g; the ultrasonic frequency is 40 kHz and the power is 500 W.
[0094] (2) placing the mixed material obtained in step (1) in a drying oven for drying to obtain a dry material;
[0095] Among them, the drying temperature is 80°C and the time is 2 hours;
[0096] (3) adding the dried material obtained in step (2) to a double-roll mill for refining to obtain a refining material; the refining time is 15 minutes and the temperature is 104°C.
[0097] (4) adding the raw material obtained in step (3) to a flat vulcanizer for tableting to obtain an EVA sheet; the tableting temperature on the flat vulcanizer is 116° C. and the time is 12 min.
[0098] (5) subjecting the EVA sheet obtained in step (4) to electron beam irradiation treatment under vacuum, and then discharging the sheet to obtain a modified EVA sheet; the vacuum condition is 0.1 Pa;
[0099] The dose of electron beam irradiation treatment is 100 kGy, and the dose rate is 180 kGy / min.
[0100] Example 2
[0101] A method for preparing a fire-resistant and stain-resistant SPC floor, which is made by laminating a modified EVA sheet with an SPC substrate;
[0102] Wherein, the modified EVA sheet and the SPC substrate are bonded by gluing;
[0103] The gluing is performed by using an adhesive;
[0104] The modified EVA sheet and the SPC substrate are bonded and then cold pressed.
[0105] The adhesive is a two-component polyurethane glue with a glue amount of 80g / ㎡;
[0106] The cold pressing pressure is 1.2 MPa and the time is 2.5 hours.
[0107] Before lamination, the surface of the SPC substrate is sanded and the thickness is adjusted to 4.5±0.05mm;
[0108] The modified EVA sheet preparation method comprises the following steps:
[0109] (1) Adding ethylene-vinyl acetate copolymer, modified nano titanium dioxide, flaky magnesium hydroxide, and an organic silane coupling agent to a mixer in sequence, stirring and mixing, and obtaining a mixed material; the mixing mass ratio of the ethylene-vinyl acetate copolymer, modified nano titanium dioxide, flaky magnesium hydroxide, and organic silane coupling agent is 72:11:5:1.1; the preparation method of modified nano titanium dioxide is:
[0110] Add palmitic acid and maleic acid to the ethanol solution in sequence, and stir and mix at a speed of 120 r / min for 30 min to obtain a treated solution;
[0111] Add nano-titanium dioxide and nano-silicon dioxide to the treatment solution in sequence, stir at 550 r / min for 2 hours, and let stand for 20 minutes;
[0112] The mixture was then ultrasonically treated for 10 minutes, filtered and dried to obtain modified nano titanium dioxide.
[0113] The mass ratio of palmitic acid, maleic acid and ethanol solution is 3.5:1.2:12;
[0114] The mass fraction of the ethanol solution is 90%;
[0115] The mixing ratio of the treatment liquid, nano titanium dioxide and nano silicon dioxide is 200 mL: 25 g: 2.5 g; the ultrasonic frequency is 40 kHz and the power is 500 W.
[0116] (2) placing the mixed material obtained in step (1) in a drying oven for drying to obtain a dry material;
[0117] Among them, the drying temperature is 80°C and the time is 2 hours;
[0118] (3) adding the dried material obtained in step (2) to a double-roll mill for refining to obtain a refining material; the refining time is 15 minutes and the temperature is 105°C.
[0119] (4) adding the raw material obtained in step (3) to a flat vulcanizer for tableting to obtain an EVA sheet; the tableting temperature on the flat vulcanizer is 117° C. and the time is 13 min.
[0120] (5) subjecting the EVA sheet obtained in step (4) to electron beam irradiation treatment under vacuum, and then discharging the sheet to obtain a modified EVA sheet; the vacuum condition is 0.15 Pa;
[0121] The dose of electron beam irradiation treatment is 105 kGy, and the dose rate is 180 kGy / min.
[0122] Example 3
[0123] A method for preparing a fire-resistant and stain-resistant SPC floor, which is made by laminating a modified EVA sheet with an SPC substrate;
[0124] Wherein, the modified EVA sheet and the SPC substrate are bonded by gluing;
[0125] The gluing is performed by using an adhesive;
[0126] The modified EVA sheet and the SPC substrate are bonded and then cold pressed.
[0127] The adhesive is a two-component polyurethane glue with a glue amount of 80g / ㎡;
[0128] The cold pressing pressure is 1.5 MPa and the time is 2.5 hours.
[0129] Before lamination, the surface of the SPC substrate is sanded and the thickness is adjusted to 4.5±0.05mm;
[0130] The modified EVA sheet preparation method comprises the following steps:
[0131] (1) Adding ethylene-vinyl acetate copolymer, modified nano titanium dioxide, flaky magnesium hydroxide, and an organic silane coupling agent to a mixer in sequence, stirring and mixing, and obtaining a mixed material; the mixing mass ratio of the ethylene-vinyl acetate copolymer, modified nano titanium dioxide, flaky magnesium hydroxide, and organic silane coupling agent is 75:13:5:1.1; the preparation method of modified nano titanium dioxide is:
[0132] Add palmitic acid and maleic acid to the ethanol solution in sequence, and stir and mix at a speed of 120 r / min for 30 min to obtain a treated solution;
[0133] Add nano-titanium dioxide and nano-silicon dioxide to the treatment solution in sequence, stir at 550 r / min for 2 hours, and let stand for 20 minutes;
[0134] The mixture was then ultrasonically treated for 10 minutes, filtered and dried to obtain modified nano titanium dioxide.
[0135] The mass ratio of palmitic acid, maleic acid and ethanol solution is 3.5:1.2:12;
[0136] The mass fraction of the ethanol solution is 90%;
[0137] The mixing ratio of the treatment liquid, nano titanium dioxide and nano silicon dioxide is 200 mL: 26 g: 2.5 g; the ultrasonic frequency is 40 kHz and the power is 500 W.
[0138] (2) placing the mixed material obtained in step (1) in a drying oven for drying to obtain a dry material;
[0139] Among them, the drying temperature is 80°C and the time is 2 hours;
[0140] (3) adding the dried material obtained in step (2) to a double-roll mill for refining to obtain a refining material; the refining time is 15 minutes and the temperature is 105°C.
[0141] (4) adding the raw material obtained in step (3) to a flat vulcanizer for tableting to obtain an EVA sheet; the tableting temperature on the flat vulcanizer is 117° C. and the time is 14 min.
[0142] (5) subjecting the EVA sheet obtained in step (4) to electron beam irradiation treatment under vacuum, and then discharging the sheet to obtain a modified EVA sheet; the vacuum condition is 0.18 Pa;
[0143] The dose of electron beam irradiation treatment is 110 kGy, and the dose rate is 180 kGy / min.
[0144] Example 4
[0145] A method for preparing a fire-resistant and stain-resistant SPC floor, which is made by laminating a modified EVA sheet with an SPC substrate;
[0146] Wherein, the modified EVA sheet and the SPC substrate are bonded by gluing;
[0147] The gluing is performed by using an adhesive;
[0148] The modified EVA sheet and the SPC substrate are bonded and then cold pressed.
[0149] The adhesive is a two-component polyurethane glue with a glue amount of 80g / ㎡;
[0150] The cold pressing pressure is 1.5 MPa and the time is 2.5 hours.
[0151] Before lamination, the surface of the SPC substrate is sanded and the thickness is adjusted to 4.5±0.05mm;
[0152] The modified EVA sheet preparation method comprises the following steps:
[0153] (1) Adding ethylene-vinyl acetate copolymer, modified nano titanium dioxide, flaky magnesium hydroxide, and an organic silane coupling agent to a mixer in sequence, stirring and mixing, and obtaining a mixed material; the mixing mass ratio of the ethylene-vinyl acetate copolymer, modified nano titanium dioxide, flaky magnesium hydroxide, and organic silane coupling agent is 76:12:5:1; the preparation method of modified nano titanium dioxide is:
[0154] Add palmitic acid and maleic acid to the ethanol solution in sequence, and stir and mix at a speed of 120 r / min for 30 min to obtain a treated solution;
[0155] Add nano-titanium dioxide and nano-silicon dioxide to the treatment solution in sequence, stir at 550 r / min for 2 hours, and let stand for 20 minutes;
[0156] The mixture was then ultrasonically treated for 10 minutes, filtered and dried to obtain modified nano titanium dioxide.
[0157] The mass ratio of palmitic acid, maleic acid and ethanol solution is 3.5:1.1:12;
[0158] The mass fraction of the ethanol solution is 90%;
[0159] The mixing ratio of the treatment liquid, nano titanium dioxide and nano silicon dioxide is 200 mL: 22 g: 2.5 g; the ultrasonic frequency is 40 kHz and the power is 500 W.
[0160] (2) placing the mixed material obtained in step (1) in a drying oven for drying to obtain a dry material;
[0161] Among them, the drying temperature is 80°C and the time is 2 hours;
[0162] (3) adding the dried material obtained in step (2) to a double-roll mill for refining to obtain a refining material; the refining time is 15 minutes and the temperature is 105°C.
[0163] (4) adding the raw material obtained in step (3) to a flat vulcanizer for tableting to obtain an EVA sheet; the tableting temperature on the flat vulcanizer is 117° C. and the time is 14 min.
[0164] (5) subjecting the EVA sheet obtained in step (4) to electron beam irradiation treatment under vacuum, and then discharging the sheet to obtain a modified EVA sheet; the vacuum condition is 0.15 Pa;
[0165] The dose of electron beam irradiation treatment is 112 kGy, and the dose rate is 180 kGy / min.
[0166] Example 5
[0167] A method for preparing a fire-resistant and stain-resistant SPC floor, which is made by laminating a modified EVA sheet with an SPC substrate;
[0168] Wherein, the modified EVA sheet and the SPC substrate are bonded by gluing;
[0169] The gluing is performed by using an adhesive;
[0170] The modified EVA sheet and the SPC substrate are bonded and then cold pressed.
[0171] The adhesive is a two-component polyurethane glue with a glue amount of 80g / ㎡;
[0172] The cold pressing pressure is 2 MP and the time is 2.5 hours.
[0173] Before lamination, the surface of the SPC substrate is sanded and the thickness is adjusted to 4.5±0.05mm;
[0174] The modified EVA sheet preparation method comprises the following steps:
[0175] (1) Adding ethylene-vinyl acetate copolymer, modified nano titanium dioxide, flaky magnesium hydroxide, and an organic silane coupling agent to a mixer in sequence, stirring and mixing, and obtaining a mixed material; the mixing mass ratio of the ethylene-vinyl acetate copolymer, modified nano titanium dioxide, flaky magnesium hydroxide, and organic silane coupling agent is 78:14:6:1.2; the preparation method of modified nano titanium dioxide is:
[0176] Add palmitic acid and maleic acid to the ethanol solution in sequence, and stir and mix at a speed of 120 r / min for 30 min to obtain a treated solution;
[0177] Add nano-titanium dioxide and nano-silicon dioxide to the treatment solution in sequence, stir at 550 r / min for 2 hours, and let stand for 20 minutes;
[0178] The mixture was then ultrasonically treated for 10 minutes, filtered and dried to obtain modified nano titanium dioxide.
[0179] The mass ratio of palmitic acid, maleic acid and ethanol solution is 4:1.5:12;
[0180] The mass fraction of the ethanol solution is 90%;
[0181] The mixing ratio of the treatment liquid, nano titanium dioxide and nano silicon dioxide is 200 mL: 30 g: 3 g; the ultrasonic frequency is 40 kHz and the power is 500 W.
[0182] (2) placing the mixed material obtained in step (1) in a drying oven for drying to obtain a dry material;
[0183] Among them, the drying temperature is 80°C and the time is 2 hours;
[0184] (3) adding the dried material obtained in step (2) to a double-roll mill for refining to obtain a refining material; the refining time is 16 minutes and the temperature is 106°C.
[0185] (4) adding the raw material obtained in step (3) to a flat vulcanizer for tableting to obtain an EVA sheet; the tableting temperature on the flat vulcanizer is 118° C. and the time is 15 min.
[0186] (5) subjecting the EVA sheet obtained in step (4) to electron beam irradiation treatment under vacuum, and then discharging the sheet to obtain a modified EVA sheet; the vacuum condition is 0.2 Pa;
[0187] The dose of electron beam irradiation treatment is 120 kGy, and the dose rate is 180 kGy / min.
[0188] Comparative Example 1
[0189] Based on Example 1, modified nano titanium dioxide is not added to the raw materials for preparing the modified EVA sheet, and the rest of the technical scheme remains unchanged.
[0190] Comparative Example 2
[0191] On the basis of Example 1, the modified nano titanium dioxide in the raw material for preparing the modified EVA sheet is replaced by unmodified nano titanium dioxide, and the rest of the technical scheme remains unchanged.
[0192] Comparative Example 3
[0193] Based on Example 1, no flaky magnesium hydroxide is added in the preparation of the modified EVA sheet, and the rest of the technical scheme remains unchanged.
[0194] SPC substrate parameters: Size: 1536*960*4.6 (mm)
[0195] Table 1 SPC substrate
[0196]
[0197]
[0198] The modified EVA sheets in Example 1 and the comparative example were tested for mechanical properties: the tensile strength and elongation at break test standards were based on ASTM D882-09;
[0199] Table 2
[0200]
[0201]
[0202] It can be seen from Table 2 that the mechanical properties of the modified EVA sheet prepared by the present invention are significantly improved. The combustion characteristics of the EVA sheets of Examples 1 to 5 and the control group were tested according to GB8410-2006, and the burning time was recorded. The test results are shown in Table 3 below:
[0203] Table 3
[0204] Combustion self-extinguishing time Example 1 72 Example 2 68 Example 3 69 Example 4 70 Example 5 67 Comparative Example 3 90 Control group 121
[0205] The control group was pure EVA sheet;
[0206] It can be seen from Table 3 that the modified EVA sheet prepared in the present invention has excellent fire resistance.
[0207] The surface water contact angle of the modified EVA sheet prepared by the present invention and the modified EVA sheet in comparative example 2 was tested using an optical contact angle meter (SZ-CAMC13, Shanghai Xuanzhun Instrument Co., Ltd.):
[0208] Table 4
[0209] Contact angle° Example 1 143 Example 2 140 Example 3 146 Example 4 141 Example 5 144 Comparative Example 2 105
[0210] It can be seen from Table 4 that the surface water contact angle of the modified EVA sheet prepared by the present invention is greatly improved, and the hydrophobicity of the surface modified EVA sheet is improved, and the improvement of the hydrophobicity can further improve its anti-fouling performance. Although the embodiments of the present invention have been shown and described, it can be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a fire-resistant and stain-resistant SPC floor, characterized in that: Made of modified EVA sheet and SPC substrate; Wherein, the modified EVA sheet and the SPC substrate are bonded by gluing; The gluing is performed by using an adhesive; After the modified EVA sheet and the SPC substrate are bonded, they are cold pressed; The modified EVA sheet preparation method comprises the following steps: (1) adding ethylene-vinyl acetate copolymer, modified nano titanium dioxide, flaky magnesium hydroxide, and an organic silane coupling agent to a mixer in sequence, stirring and mixing, and obtaining a mixed material; (2) placing the mixed material obtained in step (1) in a drying oven for drying to obtain a dry material; Among them, the drying temperature is 80°C and the time is 2 hours; (3) adding the dried material obtained in step (2) to a double-roll mill for refining to obtain a refining material; (4) adding the raw material obtained in step (3) to a flat vulcanizing machine for tableting to obtain an EVA sheet; (5) subjecting the EVA sheet obtained in step (4) to electron beam irradiation treatment under vacuum, and then discharging the sheet to obtain a modified EVA sheet; The mixing mass ratio of the ethylene-vinyl acetate copolymer, modified nano titanium dioxide, flaky magnesium hydroxide and organic silane coupling agent in step (1) is: 70-78:10-14:4-6:1-1.2; The modified nano titanium dioxide preparation method is: Add palmitic acid and maleic acid to the ethanol solution in sequence, and stir and mix at a speed of 120 r / min for 30 min to obtain a treated solution; Add nano-titanium dioxide and nano-silicon dioxide to the treatment solution in sequence, stir at 550 r / min for 2 hours, and let stand for 20 minutes; After ultrasonic treatment for 10 minutes, the product was filtered and dried to obtain modified nano titanium dioxide. The mass ratio of the palmitic acid, maleic acid and ethanol solution is 3-4:1-1.5:12; The mass fraction of the ethanol solution is 90%; The mixing ratio of the treatment liquid, nano titanium dioxide and nano silicon dioxide is 200 mL: 20-30 g: 2-3 g.
2. A method for preparing a fire-resistant and stain-resistant SPC floor according to claim 1, characterized in that: The ultrasonic frequency is 40kHz and the power is 500W.
3. A method for preparing a fire-resistant and stain-resistant SPC floor according to claim 1, characterized in that: The refining treatment time in step (3) is 15-16 minutes, and the temperature is 104-106°C.
4. A method for preparing a fire-resistant and stain-resistant SPC floor according to claim 1, characterized in that: In step (4), the temperature of the tableting on the flat vulcanizing press is 116-118° C. and the time is 12-15 minutes.
5. The method for preparing a fire-resistant and stain-resistant SPC floor according to claim 1, characterized in that: The vacuum condition in step (5) is 0.1-0.2 Pa; The dose of electron beam irradiation treatment is 100-120 kGy, and the dose rate is 180 kGy / min.
6. A method for preparing a fire-resistant and stain-resistant SPC floor according to claim 1, characterized in that: The adhesive is a two-component polyurethane glue with a glue amount of 80-100g / ㎡; The cold pressing pressure is 1-2MP and the time is 2.5 hours.
Citation Information
Patent Citations
Floor with silence pad and production process thereof
CN108915210A
Resin-base interior finish material
WO2004101672A1